2017
DOI: 10.1140/epjc/s10052-017-5392-6
|View full text |Cite
|
Sign up to set email alerts
|

Improved thermodynamics of SU(2) gauge theory

Abstract: In this work we present the results of our investigation of the thermodynamics of SU(2) gauge theory. We employ a Symanzik improved action to reduce strongly the discretisations effects, and we use the scaling relations to take into account the finite volume effects close to the critical temperature. We determine the β-function for this particular theory and we use it in the determination of different thermodynamic observables. Finally we compare our results with previous work where only the standard Wilson ac… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
23
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 54 publications
(89 reference statements)
2
23
1
Order By: Relevance
“…where the two temperatures are compared in dimensionless units as √ t 0 /N c t , and the scale t 0 for pure gauge has been computed in [48]. This value is compatible with our previous investigations in [29] at a smaller β.…”
Section: Discrete Chiral Symmetry Restoration and Quark Deconfinementsupporting
confidence: 86%
“…where the two temperatures are compared in dimensionless units as √ t 0 /N c t , and the scale t 0 for pure gauge has been computed in [48]. This value is compatible with our previous investigations in [29] at a smaller β.…”
Section: Discrete Chiral Symmetry Restoration and Quark Deconfinementsupporting
confidence: 86%
“…Zinc borate (ZB) is often used as a flame retardant synergist. [13][14][15] It is reported that zinc borates combined with metal hydroxides can function as a sintering aid of promoting formation of a strong char/ceramic residue, acting as a protecting layer for the underlying polymer. Currently ZB are predominate condensed phase flame retardants and smoke suppressants.…”
Section: Introductionmentioning
confidence: 99%
“…The triangle (cyan) symbols in the right panel denote the results of the trace anomaly at N τ = 5 given in Ref. [20]. Now, let us compare our results with the analytic prediction, namely the results of the Hard-Thermal-Loop (HTL) model.…”
Section: Simulation Results: Thermodynamic Quantitiesmentioning
confidence: 82%
“…We also summarize the data in Appendix C. Here, the error bars in the figure and the table denote only statistical errors. As a comparison, the trace anomaly (cyan-triangle 15 symbols) and the entropy density (brown-diamond symbols), which are obtained by the integral method using the improved action [20] at the fixed temporal lattice extent N τ = 5, are also shown in the figure. In T /T c ≥ 1.12, our results including the above three types of systematic errors agree with the results given by the integral method. Note that our statistical errors obtained by a fewer number of configurations are smaller than the ones in the integration methods.…”
Section: Simulation Results: Thermodynamic Quantitiesmentioning
confidence: 99%
See 1 more Smart Citation